In Vitro Mechanical Properties of Mineral Trioxide Aggregate in Moist and Dry Intracanal Environments - Å½iÅ¾ka, Radovan; ÄŒtvrtlÃk, Radim; TomaÅ¡tÃk, Jan; FaÄevicovÃ¡, Kamila; Gregor, Ladislav; Å edÃ½, JiÅ™Ã (Iranian Endodontic Journal, 2019)
Introduction: The purpose of this study was to examine the microhardness and modulus of elasticity (MOE) of White ProRoot MTA (Dentsply Tulsa Dental, Tulsa, OK) after setting in moist or dry intracanal conditions. Methods and Materials: To simulate root canal system, 14 polyethylen molds with internal diameter of 1 mm and height of 12 mm were used. These molds were filled with 9-mm thick layers of White ProRoot Mineral Trioxide Aggregate (MTA; Dentsply Tulsa Dental, Tulsa, OK). The experimental group (n=7) had a damp cotton pellet with 1.5 mm height and a 1.5 mm layer of resin composite placed on it. In control group (n=7) the whole 3 mm above MTA were filled with resin composite. The specimens were kept in 37°C and relative humidity of 80% for 4 days in order to simulate physiological conditions. Specimens were longitudinally sectioned and nanoindentation tests were carried out using Berkovich indenter at loading rate of 2 mN/s at 4×5 matrices of indents which were located in the coronal, middle and apical thirds of the specimen’s cross section, to evaluate the microhardness and modulus of elasticity of the specimen to appraise the progression of the setting process. Differences were assessed using nonparametric generalized Friedman rank sum and Wilcoxon Rank-Sum tests. Results: Statistical analysis showed that there was a significant difference in microhardness and MOE between control and experimental groups at coronal (P<0.001), middle (P<0.001) and apical (P<0.001) thirds of the simulated rod from simulated apical foramen. Kruskal-Wallis test showed no significant effect of depth on microhardness of material in experimental or control groups. Conclusion: Within limitations of this in vitro study, it seems that moist intracanal environment improves setting of MTA in various depths. Keywords: Microhardness; Mineral Trioxide Aggregate; Modulus of Elasticity; Nanoindentation